Feline hyperthroidism secondary to thyroid adenocarcinoma (Research, Society and Development, 2021)
Hyperthyroidism refers to the increase in functional thyroid hormones, thyroxine (T4) and triiodothyronine (T3). Most cases of hyperthyroidism are caused by thyroid adenoma or multinodular adenomatous hyperplasia, affecting one or both lobes of the thyroid gland. Less than 5% of cases occur as a result of thyroid carcinoma. Thus, this study aimed to present a case report about feline hyperthyroidism caused by thyroid carcinoma, in an 11-year-old male feline. The animal had a history of anorexia, vomiting and diarrhea about a month ago. Complete blood count, biochemical, abdominal ultrasound and CT scan of the cervical region were requested. Laboratory and physical examinations indicated strong signs of hyperthyroidism, such as erythrocytosis, increase in total T4 and increase in the palpable volume of the thyroid, in addition to tomographic examination indicative of neoplastic process in the left thyroid lobe, without involvement of adjacent structures. The treatment of choice was surgery with the modified extracapsular technique with a cervical approach (thyrodectomy with preservation of the parathyroid glands). After surgical procedures and supportive treatment, the animal presented remission of clinical signs.